PENGEMBANGAN MODEL PEMBELAJARAN SAINTIFIK BERBASIS GOOGLE EARTH UNTUK MENINGKATKAN HASIL BELAJAR PEMETAAN GEOLOGI - Oktavianto, Dwi Angga (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2020)
This research was conducted to produce a learning model for geology learning at the Vocational High School level. The learning model is generated by utilizing the development of geospatial technology, namely Google Earth. This research also aims to; (1) disclose student learning outcomes before and after using the Google Earth-based learning model; (2) developing a scientific learning model based on Google Earth; (3) testing the effectiveness of the resulting model. This research is a Research and Development (RD) research conducted at SMK Negeri 1 Binuang in September 2019. The research subjects were 27 students of class XII Mining Geology. Research data obtained from instruments in the form of questionnaires, observation sheets and student learning outcomes which are a combination of performance scores and project values. Data analysis using; lesson content analysis, product development feasibility analysis, and effectiveness analysis using the Wilcoxson signed ranks test. The results showed that; (1) the value of student learning outcomes at posttest was higher than at pretest; (2) Google Earth-based scientific learning model has six learning steps; and (3) The significance value with the Wilcoxson signed ranks test shows the number 0.000 which, if interpreted, means that the Google Earth scientific-based learning model is effectively used. This model is proven effective in lessons that have material in the form of spatial data (spatial reference).Keywords: Learning Model; scientific; Google Earth; Learning Outcomes